Youth sport development pathways and experiences of NCAA Division I women's college soccer players - Hardell, E. B. (San José State University, 2017)
As youth sport has become increasingly professionalized, many believe that the route to elite level play is through early specialization. Early specialization is a contentious issue, and many risk factors have been associated with high levels and intensities of training in youth. Youth today participate in highly competitive sport in pursuit of elite levels of play, recognition, and financial gain. Early specialization is thought to be a requirement for advancement, yet little is known about the early experiences of team sport athletes who grew up in the US. This is the story of 15 elite female athletes who "made it" to Division I soccer. The study offers us a window into the professionalized and commercialized world of youth soccer. It is a description of the childhood and adolescent journeys through sport and spans 10+ years of development. Through its telling, we learn about the expensive pay-to-play pipeline in soccer, we hear of the differences in opportunities that exist between social classes, and we confirm theories of expertise development. We learn that whether a young athlete specializes early or chooses to play multiple sports has little relevance to her progression to Division I. Through our thematic analysis of injury, we see how young athletes routinely play through injury, hide injury from coaches, and carry injury forward into their collegiate playing careers.